Three new species of Onychiuridae Lubbock, 1871(Collembola, Poduromorpha) from Iran - Kaprus, Igor; Shayanmehr, Masoumeh; Lafooraki, Elham Yoosefi (Zootaxa, 2017)
Iranian Onychiuridae found so far in various provinces by different researchers have been reviewed. At present, sixteen species belonging to the family Onychiuridae are recorded from Iran, six of which need confirmation. Three new species from different tribes of the family, namely Heteraphorura iranica sp. nov., (Hymenaphorurini), Protaphorura golestanica sp. nov. (Protaphorurini) and Spinonychiurus persicus sp. nov. (Thalassaphorurini), are described and illustrated. H. iranica sp. nov. belongs to the oriental species-group of the genus characterized by granulated vesicles in PAO, P. golestanica sp. nov.––to the group of Protaphorura species without pso on subcoxa 1 of all legs and with 2+2 pso ventrally on the head, S. persicus sp. nov.––to the group of Spinonychiurus species with 11 chaetae in distal whorl of tibiotarsi. A key of the Palearctic species of Heteraphorura is provided.